The effect of motivational determinants on elite Wrestlers’ ıntentions to continue in sport: The mediating role of enjoyment - Burhan Özkurt; Ersin Eskiler (PLoS ONE, 2026)
This study aimed to examine the associations of motivational determinants, including goal orientation, satisfaction of basic psychological needs, and motivation, with elite wrestlers’ intention to continue in sport, and to evaluate the indirect role of enjoyment in these associations. An explanatory sequential mixed-methods design was used. The quantitative sample comprised 374 elite wrestlers competing under the Turkish Wrestling Federation, and the qualitative sample comprised 16 volunteer elite wrestlers competing in freestyle and Greco-Roman wrestling. Quantitative data were collected using validated scales measuring goal orientation, basic psychological need satisfaction, sport motivation, enjoyment, and intention to continue in sport, and were analyzed using descriptive statistics and structural equation modeling through SPSS and AMOS. Qualitative data were collected through a semi-structured interview form and analyzed using content and descriptive analysis techniques in MAXQDA 2020. The quantitative findings showed that goal orientation, satisfaction of basic psychological needs, motivation, and enjoyment had significant direct, indirect, and total associations with intention to continue in sport. Enjoyment showed an indirect role in these associations, and the proposed model explained 41% of the variance in intention to continue in sport. The qualitative findings were classified under the theme “Factors Associated with Intention to Continue in Sport” and grouped into positive and negative factors with internal and external subcategories. Internal positive factors included commitment and passion, achievement goals, and enjoyment, whereas external positive factors included reference groups, coach interaction, and social support. Negative factors included failure, negative psychological processes, injustice, sport-specific difficulties, and lack of resources. Overall, the findings indicate that elite wrestlers’ intention to continue in sport is associated with motivational, emotional, social, and contextual factors. The qualitative findings further suggest that these factors are reflected in athletes’ experiences regarding sport continuation.